2022
DOI: 10.1021/acs.jmedchem.1c01740
|View full text |Cite
|
Sign up to set email alerts
|

Highly Antiproliferative Latonduine and Indolo[2,3-c]quinoline Derivatives: Complex Formation with Copper(II) Markedly Changes the Kinase Inhibitory Profile

Abstract: A series of latonduine and indoloquinoline derivatives HL 1 – HL 8 and their copper(II) complexes ( 1–8 ) were synthesized and comprehensively characterized. The structures of five compounds ( HL 6 , [CuCl(L 1 )(DMF)]·DMF , [CuCl(L 2 )(CH 3 OH)] , … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(42 citation statements)
references
References 118 publications
(266 reference statements)
0
42
0
Order By: Relevance
“…3,4 Numerous studies have reported that copper complexes may have excellent anticancer activity and low toxicity owing to their different antitumor mechanisms from those of platinum-based chemotherapeutic drugs. 5,6 In addition, copper(II) complexes are prone to redox reactions under physiological conditions, and intracellular cytotoxic reactive oxygen species (ROS) will be generated by the mutual conversion of oxidized state (Cu 2+ ) and reduced state (Cu + ). 7,8 Therefore, copper(II) complexes are considered as potential candidates for anticancer therapy and medical applications.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Numerous studies have reported that copper complexes may have excellent anticancer activity and low toxicity owing to their different antitumor mechanisms from those of platinum-based chemotherapeutic drugs. 5,6 In addition, copper(II) complexes are prone to redox reactions under physiological conditions, and intracellular cytotoxic reactive oxygen species (ROS) will be generated by the mutual conversion of oxidized state (Cu 2+ ) and reduced state (Cu + ). 7,8 Therefore, copper(II) complexes are considered as potential candidates for anticancer therapy and medical applications.…”
Section: Introductionmentioning
confidence: 99%
“…However, coordination of these ligands to copper(II) might induce a new mechanism of action. 48 In particular, fully distinct inhibitory profiles in enzyme inhibition assays were disclosed recently for indolo[3,2- c ]quinoline-based ligand and its copper(II) complex, 34 highlighting a special role of copper(II) in the underlying mechanism of cytotoxicity. The anticancer activity of copper(II) complexes 1 – 4 is mostly due to their redox activity (when compared to redox silent ligands HL 1 – HL 4 ) which resulted in the generation of cytotoxic ROS and induction of ER stress (vide infra).…”
Section: Resultsmentioning
confidence: 99%
“…The in vitro antiproliferative activity of novel organic compounds HL 1 −HL 4 and corresponding copper(II) complexes 1−4 was tested in the breast cancer cell line MDA-MB-231, hepatocellular carcinoma cell line LM3, and human embryonic kidney cell line HEK293 and then compared to those of the previously reported paullones HL 5 −HL 7 and copper(II) complexes 5−7, 39,44 as well as latonduines HL 8 −HL 11 and copper(II) complexes 8−11. 34 The two cancer cell lines were reported to exhibit quite aggressive behavior in patients, high rates of metastasis, and proliferation. 45,46 The in vitro anticancer activity was determined by the colorimetric MTT assay with an exposure time of 72 h. The IC 50 values of compounds of interest are listed in Table 1.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past several decades, because copper (Cu) is an essential metal in the human body and plays a vital role in biological functions, Cu compounds have been extensively studied as the promising next-generation anticancer metal drugs. Interestingly, many studies have shown that metal compounds can kill cancer cells through multiple mechanisms, overcome the resistance of cancer cells to cisplatin, and inhibit their metastasis. Currently, it has been one of the most effectively strategies for the treatment of cancer through acting on the different components of the tumor micro-environment (TME). , Therefore, we may overcome the resistance of NSCLC cells to cisplatin and inhibit their metastasis by rationally designing a new Cu agent that acts on the different components in the TME.…”
Section: Introductionmentioning
confidence: 99%